The Potential of Neonatal Organ Donation in Central Sweden - Emil Bluhme; Ewa Henckel; Boubou Hallberg; Carl Jorns (Cell Transplantation)
Pediatric organ transplant recipients have a higher risk for wait list mortality due to the scarcity of size matched organs. Neonatal organ donation could potentially ameliorate the discrepancy but is currently not implemented in Sweden. This study aims to evaluate the potential of neonatal organ donation in central Sweden using a standardized protocol with organ specific criteria. Data on 2,061 neonates who deceased in central Sweden from 2006 to 2016 were collected; 308 neonates met criteria for possible donation. Medical records of all possible donors were reviewed, identifying 85 potential donors. Main cause of death was hypoxic ischemic encephalopathy 47% (n = 40). Median weight was 2,355 (IQR: 1,953) g, with 31% receiving inotropic support. Median creatinine of 72 (IQR: 67) µmol/l, urine production 3 (IQR: 2.2) ml/kg/h, ALT 0.51 (IQR: 1.5) µkat/l, and AST 1.7 (IQR: 3.1) µkat/l. Criteria for kidney donation was met in 39 potential neonatal, 29 for liver and 18 for heart, corresponding to a potential increase of 1.9, 1.4, and 0.9 donors PMP per year, respectively. In total, 16 neonates had a catastrophic neurological injury in combination with lack of brainstem reflexes, indicating plausibility of donation after brain death. Expanding organ donation into the neonatal period in Sweden could lead to an increase in organs available for transplant.